Structure Investigations of NiO/Al2O3/B2O3/SiO2 Composite Based on PVA Using Sol-Gel Processing and the Electrospinning Technique - Sevim, Fatih; Sevimli, Esma (Asian Journal of Chemistry, 2014)
Nickel oxides are well-studied materials due to its excellent chemical stability, as well as optical, electrical and magnetic properties. It has been used as battery materials, electrochromic layers, catalysis materials, etc. Among them electrochromic device using as NiO anodic material are recognized for their durability compared with other anodic EC materials, colouration efficiency and low material cost. Therefore it is well suitable in conjunction with electro chromic tungsten oxide as colouring electrode. Important information regarding dynamics, structure and exchange rates between different spin groups that might exist in a system can be extracted from their NMR signals. To accomplish this, one often needs to decompose different NMR signal components within the final spectrum.